Analisa Market Basket Analysis untuk Melihat Pola Transaksi Customer Menggunakan Algoritma Apriori dan FP-Growth - Griya Jitri Pabutungan; Hindriyanto Dwi Purnomo (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Online sales are considered an alternative approach that can positively impact product marketing. But the more online shops, the greater the competition in the business world. From the problems above, so that the store can survive among busy competitors, a strategy that is qualified as an effort to attract customer attention is needed. One effort that can be done is to look at customer patterns or tendencies during transactions. Knowing this is expected to provide additional information to stores to increase loyalty and meet customer needs so that online business stores that are built can last a long time. Based on the description that has been explained, the purpose of writing this research is to find customer spending patterns so that it can support XYZ company as one of the retail application managers in creating business strategies that can be used to attract customer interest using the market basket analysis method and the help of the a priori algorithm and fp-growth as a comparison. The market basket looks at product categories often purchased together in one receipt by customers. This study uses transaction data of 34,159,477, a minimum confidence value of 0.2, and a minimum support of 0.01 for both algorithms. The results of the two algorithms using the same minimum value give the same result in the form of 10 association rules itemset.